PENGAMANAN PESAN MENGGUNAKAN TEKNIK STEGANOGRAFI DENGAN ALGORITMA LEAST SIGNIFICANT BIT (LSB) - Angga Aditya Permana (Universitas Bunda Mulia, 2020)
Steganography is a technique or art to hide a secret message into a cover so that the existence of the secret message cannot be known by other people or third parties who do not have the ability to know the contents of the secret message. The Least Significant Bit (LSB) method is one of the methods used in steganography to hide a message by changing the value of the rightmost bit of a stego cover with a secret message. The purpose of this study was to hide a text message into an image using the LSB method.